Is waist-calf circumference ratio associated with frailty in older adults? Findings from a cohort study - Miao Dai; Quhong Song; Jirong Yue; Taiping Lin; Wei Jie; Xiang Wang; Ning Ge (BMC Geriatrics, 2023)
Abstract Background The waist-calf circumference ratio (WCR) has been suggested as a potential indicator of visceral adiposity. Nevertheless, the relationship between WCR and the risk of frailty remains unclear. Therefore, our study aimed to investigate the association between WCR and longitudinal changes in WCR with frailty risk in older adults. Methods We included 2359 participants aged ≥ 65 years without frailty (frailty index [FI] ≤ 0.21) from the Chinese Longitudinal Healthy Longevity Survey in the 2014 wave. The follow-up was conducted in 2018. We investigated the relationship of WCR, waist circumference (WC), and calf circumference (CC) with frailty using both the Cox proportional hazards model and the generalized estimating equation (GEE). Results During a median follow-up of 4.0 years, 668 (28.2%) frailty occurred. Those with higher WCR and WC had a significantly increased risk of frailty (fifth quintile compared with first quintile: hazard ratio [HR] = 1.59, 95% confidence interval [CI] 1.24–2.04 for WCR; HR = 1.69, 95% CI 1.27–2.24 for WC), whereas those in the fourth quintile of CC had a lower likelihood of developing frailty compared to those in the first quintile (HR = 0.67, 95% CI 0.50–0.89). Interaction analyses showed that the effects of WCR on frailty were more pronounced in females (P-interaction = 0.016). GEE analyses revealed that increased WCR and WC were associated with a higher risk of frailty (odds ratio [OR] = 1.74, 95% CI 1.43–2.12 for WCR; OR = 1.03, 95% CI 1.02–1.04 for WC), while CC showed opposite results (OR = 0.95, 95% CI 0.93–0.97). Conclusions A higher WCR and WC, as well as a lower CC, were significantly associated with higher frailty. Of these measures, WCR demonstrated the strongest association with frailty, suggesting that having a combination of high central fat and low lean body mass may increase the risk of developing frailty.